Answer:
x = -9, 0 = -1, x \ne 0
Explanation:
[-54/x = 6 0x = 9]
Isolate x for - 54/x = 6 : x = -9
-54/x = 6
Multiply both sides by x
-54/x = 6x
Simplify - 54/x x : -54
-54x x = 6x
Multiply fractions: a . b/c = a . b/c
= -54x/x
Cancel the common factor: x
= -54
- 54 = 6x
Switch sides
6x = -54
Divide both sides by 6
6x/6 = -54/6
Simplify
6x/6 = -54/6
Simplify 6x/6: -9
6x/6
Divide the numbers: 6/6 = 1
= x
Simplify
-54/6
Apply the fraction rule: -a/b = -a/b
= -54/6
Divide the numbers: 54/6 = 9
= -9
x = -9
Verify solutions
Find underfined (singularity) point: x = 0
Take the denominator (s) of - 54/x and compare to zero
x = 0
Combine undefined points with solutions:
x = -9
Substitute x = -9
[ o(-9) = 9]
Simplify
0(-9) = 9
Simplify
0(-9): -90
Remove parentheses: (-a) = -a
= -0 . 9
-90 = 9
[-90 = 9]
Isolate o for -90 = 9 : o = -1
-90 = 9
Divide both sides by -9
-90/-9 = 9/-9
Simplify
0 = -1
The solutions to the system of equations are:
x = -9, 0 = -1, x \ne 0